UJI VALIDITAS ISI TARUMANAGARA CAREER DECISION SELF-EFFICACY SCALE - Jessyca Jessyca; P. Tommy Y. S. Suyasa (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
In the process of career decision making, being confidence in the chosen career (career decision making self-efficacy [CDMSE]) is the final stage also an important construct to be success in career. Since adolescents, especially in high school, students is required to choose a field of specialization which is the beginning of their future career decision. It is important for teenagers to have confidence in their chosen career so that they’re motivated to explore further their choice and success in it. The aim of this research is to provide recommended scale that can be used in career decision making self-efficacy’s research. The test development is carried out through content validation study by referring to the selected scale from systematic review method. Content validation study is done through expert judgment. Some of the modifications include the adjustment to language/grammar, culture, meaning, type of scaling method, and dimensions also items based on the career decision making self-efficacy’s case/problem in Indonesia, especially for adolescence in high school. The result of this study recommended measuring instrument named Tarumanagara Career Decision Self-Efficacy Scale (Tarumanagara CDSES). This scale consists of 30 items, includes five items of Occupational Information dimension, five items of Goal Selection dimension, four items of Self-Appraisal dimension, three items of School Achievement dimension, four items of Problem-Solving dimension, five items of Social Support dimension, and four items of Planning dimension. Dalam proses keputusan karir, keyakinan terhadap karir yang akan dipilih (career decision making self-efficacy [CDMSE]) adalah tahap akhir dan merupakan konstruk yang penting dalam kesuksesan karir. Remaja, dalam hal ini sejak jenjang pendidikan SMA telah dituntut untuk memilih bidang peminatan yang merupakan awal proses keputusan karir di masa depan. Penting bagi remaja untuk memiliki keyakinan terhadap karir yang hendak dipilih guna memiliki motivasi untuk mengeksplorasi lebih jauh pilihannya sehingga dapat sukses dalam karir yang dijalani. Tujuan penelitian ini adalah untuk menghasilkan alat ukur yang dapat direkomendasikan untuk digunakan dalam penelitian mengenai konstruk keyakinan terhadap keputusan karir. Pengembangan alat ukur dilakukan melalui studi validitas isi dengan mengacu pada alat ukur terpilih dari hasil tinjauan sistematis. Metode uji validitas isi dilakukan melalui penilaian pakar/ahli. Beberapa modifikasi yang dilakukan adalah penyesuaian tata bahasa, budaya, makna, jenis skala pengukuran, dan butir serta dimensi berdasarkan latar permasalahan keyakinan terhadap keputusan karir di Indonesia, khususnya pada siswa SMA usia remaja. Hasil penelitian merekomendasikan alat ukur Tarumanagara CDSES yang terdiri atas 30 butir dengan rincian lima butir dalam dimensi Occupational Information, lima butir dalam dimensi Goal Selection, empat butir dalam dimensi Self-Appraisal, tiga butir dalam dimensi School Achievement, empat butir dalam dimensi Problem Solving, lima butir dalam dimensi Social Support, dan empat butir dalam dimensi Planning.